P104 Lung cancer with co-existing interstitial lung disease: incidence, treatment and outcomes. (11th November 2022) - Bhatnagar, M; Farthing, L; Storey, C; Murphy, C; Haney, S
Abstract : Introduction and Objectives: Interstitial lung disease is associated with an increased risk of lung cancer. The diagnosis and management of lung cancer in these patients is challenging due to poor lung function and performance status, as well as increased risk of toxicity/acute exacerbation of ILD with treatment. Little data is available on the toxicity of treatment in European patients. We aimed to assess the prevalence of interstitial lung disease in patients with lung cancer and studied their diagnostic pathway, treatment and clinical outcomes. Methods: 2 large secondary care trusts took part in the study. Patients were identified from the lung cancer registry at each site and their clinic letters and presenting radiology screened for interstitial lung disease. MDT outcomes and case notes were reviewed. Data presented are from 2017. Results: 623 patients were diagnosed with lung cancer in 2017 across the 2 trusts. 43/623 (6.9%) had evidence of interstitial lung disease on presentation, but ILD was previously diagnosed in only 9 of these. CT pattern was recorded in 31/43 (72%) of whom 11 had a UIP pattern. 29(67%) had pathological confirmation, of whom 28(89%) of ILD patients had non-small cell lung cancer on histology. Mean FVC was 88% predicted. 5(11.6%) patients were planned for surgery, 4(9.3%) chemotherapy, 9(20.9%) radiotherapy, 7(16.2%) combined treatments and 17(39.5%) best supportive care. Grade 4 or 5 pulmonary toxicity was recorded in 5 patients: 1 after surgery, 2 post-radiotherapy (20% of those receiving radiotherapy to lung), 2 after chemo/immunotherapy. Conclusions: The prevalence of interstitial lung disease in lung cancer patients was high. Most of these were not previously diagnosed and often not recognised even at MDT. Pulmonary toxicity of treatment was a factor in some cases. Overall rates of anticancer treatment were not different to the standard lung cancer population.